USE OF INDICATORS ANTHROPOMETRIC REFERENCE IN ELDERLY IN ASSESSMENT OF LEVELS OF HEALTH (Fiep Bulletin - online, 2013)
A significant number of studies have been carried out considering the use of anthropometry in assessing the health status of the elderly population. Where recent developments show the importance of anthropometry throughout the life cycle, not just for individual assessments, but also to reflect the state of health and social and economic situation of the population. This study aimed to perform a systematic review on the application of anthropometric indicators as a reference in evaluating the health of elderly populations. The search was performed in the databases Pubmed, Scielo and Bireme. The selection was made by inclusion criteria, which are: original articles published in English or Portuguese. And the descriptors used in the identification of the articles were: "anthropometric indicators and the elderly." Recent studies indicate that the elderly represent the fastest-growing populations in the world, with the particularity of being a heterogeneous group, prompting the need for further research where the concept functional or biological age should gain more attention in the elderly. Within a single population, individual variation is enhanced because of varying rates of aging from person to person and the physiological system. The use of reference values ??of anthropometric indicators needs a little revision due to existence of normative data for older people in developing countries like Brazil, recognizing the limitations and the numerous gaps when using the interpretation of anthropometric data in elderly generally, without taking into account the existing pathophysiological changes in the aging process.
Keywords: Anthropometry; Seniorsç; Health indicators.